STRES AKADEMIK DAN OPTIMISME TERHADAP RESILIENSI AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Iffa Alifah; Magdalena Hanoum; Lucky Purwantini (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
The purpose of this study was to examine the relationship and influence of academic stress and optimism on academic resilience. This research is a quantitative research with correlational type involving 91 final year students at Universitas Islam “45” Bekasi. The sampling technique used a non-probability sample technique with a proportionate strafied random sampling technique. This study uses an academic resilience scale with a reliability value of 0.891 Chronbach's Alpha, an academic stress scale with a Chronbach's Alpha reliability value of 0.943 and an optimism scale with a Chronbach's Alpha reliability value of 0.895. The data analysis technique used Rank- Spearman correlation test and multiple linear regression. This study found that there is a positive relationship between academic stress and optimism on academic resilience. Then, there is also an influence between academic stress and optimism on academic resilience with an effective contribution of 13.8% for final year students at Universitas Islam